Compartmentalization of TNF and IL-6 in meningitis and septic shock - Anders Waage; Alfred Halstensen; Terje Espevik; Petter Brandtzæg (Hindawi Limited, 1993)
We examined the compartmentalization of bioactive tumour necrosis factor (TNF) and interleukin 6 (IL-6) to the subarachnoid space and systemic circulation in patients with meningococcal meningitis and septic shock/bacteraemia. In patients with meningitis, median levels of TNF in 31 paired samples of cerebrospinal fluid (CSF) and serum were respectively 783 pg/ml and below detection limit (p < 0.001) and median levels of IL-6 were 150 ng/ml and 0.3 ng/ml (p < 0.0001). In patients with septic shock without meningitis, median levels in paired samples of CSF and serum were respectively below detection limit and 65 pg/ml (not significant, (ns)) (TNF, eleven patients) and 1.3 ng/ml-3 ng/ml (ns) (IL-6, nine patients). The data show that TNF and IL-6 are localized to the subarachnoid space in patients with meningitis although the blood-brain barrier is penetrable to serum proteins. On the other hand, patients with septic shock tend to have cytokines in both serum and CSF.